Process Validation of Analytical method Development and Validation for Omeprazole Capsules and Blend - D.KUMARASWAMY; B.STEPHENRATHINARAJ; CH.RAJVEER; S.SUDHARSHINI; P. RAJASRIDHAR RAO (International Journal of Pharma and Bio Sciences, 2010)
A new simple, rapid and reliable UV Spectrophotometry method was developed and validated for the estimation of Omeprazole in blend & Capsules formulations. The method was based on simple UV estimation in cost effective manner for regular laboratory analysis. The instrument used was Perkin Elmer, UV Spectrophotometer (Lambda 25) and using 0.1 N NaoH as solvent system. Sample were analysed using UV Win Lab 5.2.0 Software and matched quartz cells 1 cm and was monitored at 302 nm. Linearity was obtained in the concentration range of 2 - 10 mg mL–1 for Omeprazole. The validation parameters, tested in accordance with the requirements of ICH guidelines, prove the suitability of this method. Spectrophotometric interferences from the Capsules excipients were not found. The results of blend uniformity and content uniformity, done on process validation batches samples.